Pedagogical Implications of Corpus-based Approaches to ELT in Pakistan (Journal of Education and Educational Development, 2020)
The advent of corpora has opened new vistas for language study and restructured linguists’ and academicians’ approaches to lexicography and English language teaching (ELT). After 1980s, the use of online language corpora and computer tools garnered tremendous attention of English language teachers and academicians. Keeping in view the modern trends and needs of learners, this research focused on the practical implications of online corpora for ELT and its utility in the Pakistani context. Michigan Corpus of Academic Spoken English (MICASE) is used as a reference corpus for this research. MICASE is a collection of nearly 1.8 million words of transcribed speech (almost two hundred hours of recording). The transcribed data of MICASE includes wide range of speech events like seminars, lectures, advisory meetings and lab sessions. The study identified the utility of lexical items at syntactic level and its usage in various contexts. Furthermore, the layers of meanings and uses of lexicons through in-depth study of right and left collocates were explored in the reference corpus. The results showed that lexicons can be used as noun, verb and adjective depending upon the context of the study and right and left collocates play a significant role in understanding the meanings of lexical items in various contexts. Thus, this strategy can be fruitful for English language learners and academic discourse community who are interested in understanding the versatile uses of lexical items and their contextual meaning.